How Work Commitment, Work Discipline, and Workload Mediate the Relationship Between Organizational Culture and Employee Performance?: Empirical Evidence in Land Office of Southeast Sulawesi Province - Mahmud, Irwanto; Kalsum, Ummy; Abbas, Bakhtiar (Economic and Business Horizon, 2023)
This research explores the intricate dynamics of employee performance within the National Land Agency of Southeast Sulawesi Province, focusing on the influence of work commitment, work discipline, and workload among 109 civil servants. Findings reveal that collectively, work commitment, work discipline, and workload significantly impact employee performance, with improved work commitment and work discipline, alongside reduced workload, enhancing task engagement, work attitude, quality, initiative, cooperation, quantity, self-development, and leadership. Individually, work commitment positively influences performance, emphasizing the importance of an emotional attachment to the workplace. Work discipline emerges as a dominant factor affecting performance, underscoring the significance of adherence to rules and avoidance of counterproductive behaviors. Surprisingly, workload's impact on performance was insignificant, despite employees facing challenges related to task difficulty and time pressure. These insights offer valuable guidance for organizational leaders seeking to optimize employee performance in the National Land Agency of Southeast Sulawesi Province.